PREMI ASURANSI JIWA BERJANGKA NAIK DENGAN MENGGUNAKAN HUKUM DE MOIVRE - Antony Wijaya; Hasriati '; Musraini ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the premium for participants whose age are years old, who participate in increasing term life insurance program. Premium calculated are a single premium, the annual premium, and the premium with times payment a year. The premiums consist of a single net premium calculation, the annual net premium, and net premium payments with times in a year that are influenced by due life annuity and management expense insurance. Premium calculation used in this article of actuarialassumptions is the De Moivre of law.